Exploring the rationale for combining ionizing radiation and immune checkpoint blockade in head and neck cancer. Issue 6 (20th February 2018) - Morisada, Megan; Chamberlin, Michael; Allen, Clint
Abstract: Background: The ability of radiation to enhance antitumor immunity under specific experimental conditions is well established. Here, we explore preclinical data and the rationale for combining different radiation doses and fractions with immune checkpoint blockade immunotherapy. Methods: We conducted a review of the literature. Results: The ability of high‐dose or hypofractionated radiation to enhance antitumor immunity resulting in additive or synergistic tumor control when combined with checkpoint blockade is well studied. Whether low‐dose daily fractionated radiation does the same is less well studied and available data suggests it may be immunosuppressive. Conclusion: Although daily fractionated radiation is well established as the standard of care for the treatment of patients with head and neck cancer, how this radiation schema alters antitumor immunity needs further study. If the radiation doses and fractions alter antitumor immunity differently can have profound implications in the rational design of clinical trials investigating whether radiation can enhance response rates to immune checkpoint blockade.